Strategi Positioning Masjid Al-jabbar sebagai Destinasi Wisata Religi yang Menunjang Kesehatan Mental - Ira Hasianna Rambe; Mufti Fauzi Rahman; Dedeh Dahlia; Linda Widyastuti (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to analyze how visitors’ experiences shape the positioning of Al-Jabbar Grand Mosque as a modern religious destination that supports mental health. The research focuses on emotional experiences, perceptions of the physical environment, social interactions, and the meanings constructed by visitors during their time in the mosque area. A qualitative approach with a phenomenological design was used, as this study seeks to understand the subjective meanings of visitors’ experiences in depth. The informants consisted of 22 participants 9 male and 13 female visitors selected through purposive sampling. Data were collected through in-depth interviews and analyzed using processes of data reduction, thematic categorization, and meaning interpretation. The results show that visitors experience a strong sense of tranquility, comfort, and psychological restoration, including a “being away” sensation from the pressures of daily routines. The mosque’s architecture, lakeside landscape, and open-space ambience contribute significantly to calming spiritual and psychological experiences. Social interactions between visitors and mosque staff further reinforce positive perceptions of the mosque environment. These findings indicate that the positioning of Al-Jabbar Mosque naturally emerges through visitors’ authentic experiences rather than through formal promotional strategies. This study is expected to serve as a reference for mosque administrators in developing modern religious spaces that support the emotional well-being of the community.